Oriented strand board from rubberwood and juvenile sentang / Suffian, M ... [et al.] - M, Suffian; R, Rafeadah; S, Rahim; B, Saimin; S, Jalali; P, Nordin (2004)
The effects of wood species namely rubberwood and sentang (Azadirachta excelsa) to oriented strand board (OSB) has been investigated. The species were different in term of wood density. Series of OSBs were produced using the selected species at board density of 650 kg/m3 During the manufacture, a phenol formaldehyde resin with solids content of 54% was used as cinder at resin loading of 3,5 and 7% of the board weight. The boards' properties namely modulus of rupture (MOR), modulus of elasticity (MOE), internal bond (IB) and thickness swelling (TS) were determined according to European Standards. The effects of wood species to the boards' properties were significant. The appropriate parameters of OSB using rubberwood and sentang have been suggested in this study.